Ecological consequences of a single introduced species to the Antarctic: terrestrial impacts of the invasive midge Eretmoptera murphyi on Signy Island. (May 2023) - Bartlett, Jesamine C.; Convey, P.; Newsham, K.K.; Hayward, S.A.L.
Abstract: The nutrient-poor soils of Antarctica are sensitive to change. Recent increases in the number of anthropogenic introductions mean that understanding the impact of non-native species on Antarctic soils is pertinent, and essential for developing future risk assessments and management strategies. Through comparative baseline assessments of vegetation, microbes, soil chemistry, substrate composition and micro-arthropod abundance, this study explored if there are detectable terrestrial ecosystem impacts resulting from the introduction of the chironomid midge Eretmoptera murphyi to Signy Island in maritime Antarctica. The key finding was that E. murphyi is the likely driver of an increase in inorganic nitrogen availability within the nutrient-poor soils in which it occurs. When compared with the levels of inorganic nitrogen present in soils influenced by native vertebrate wildlife aggregations, the increase in local nitrate availability associated with E. murphyi was similar to that caused by deposits from seals and giant petrel colonies. Overall, available nitrate has increased by three- to five-fold in soils colonised by the midge, relative to undisturbed soils. This may ultimately impact rates of decomposition as well as the native plant and micro-arthropod communities of Signy Island. Highlights: An invasive midge to Antarctica is likely to be increasing soil nitrate availability. Colonised soils have a three- to five-fold increase in nitrate compared to uncolonised areas. A single insect species is capable of disrupting polar soils with implications for soil development.